2021
DOI: 10.1029/2021gl092696
|View full text |Cite
|
Sign up to set email alerts
|

High‐Latitude Stratospheric Aerosol Geoengineering Can Be More Effective if Injection Is Limited to Spring

Abstract: Stratospheric aerosol geoengineering focused on the Arctic could substantially reduce local and worldwide impacts of anthropogenic global warming. Because the Arctic receives little sunlight during the winter, stratospheric aerosols present in the winter at high latitudes have little impact on the climate, whereas stratospheric aerosols present during the summer achieve larger changes in radiative forcing. Injecting SO2 in the spring leads to peak aerosol optical depth (AOD) in the summer. We demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
87
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(92 citation statements)
references
References 68 publications
(115 reference statements)
5
87
0
Order By: Relevance
“…Visioni et al ( 2020) found that regional climate response would be significantly different with injection at the same location and height but different season. Lee et al (2021) find that spring injections of stratospheric aerosol are most efficient in restoring sea ice as the injected particles stay in the stratosphere throughout the summer. The exploration of climate response to different seasonal patterns of aerosol addition, together with different latitudinal and altitudinal distributions of aerosol addition, merits further investigation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Visioni et al ( 2020) found that regional climate response would be significantly different with injection at the same location and height but different season. Lee et al (2021) find that spring injections of stratospheric aerosol are most efficient in restoring sea ice as the injected particles stay in the stratosphere throughout the summer. The exploration of climate response to different seasonal patterns of aerosol addition, together with different latitudinal and altitudinal distributions of aerosol addition, merits further investigation.…”
Section: Discussionmentioning
confidence: 87%
“…Many studies have investigated the climate response to SAI, and a subset of them have investigated the injection of SO 2 into the tropical lower stratosphere (Berdahl et al, 2014;Jones et al, 2010;Kravitz et al, 2011;Rasch, Tilmes, et al, 2008;Robock et al, 2008). Climate effect of injecting SO 2 into the high-latitude stratosphere, such as over the Arctic, has been also examined (Jackson et al, 2015;Lee et al, 2021;Robock et al, 2008). More recent studies examine climate response to SO 2 injections at multiple latitudes.…”
mentioning
confidence: 99%
“…In practice, an SAI implementation would be much more sophisticated than G4, for example, aiming to preserve existing hemispheric temperature balance, as well as equator-to-pole temperature gradients (Kravitz et al, 2016), and with seasonally varying injection rates. These types of implementations might be expected to for example, well preserve Arctic sea ice (Lee et al, 2021), along with and AMOC and Greenland ice sheet mass balance (Tilmes et al, 2020). Although detailed analyses of differences between this kind of SAI deployment and the simple version applied here have not been done, they appear to be second order compared with the impacts introduced by temperature rises due to greenhouse gas scenarios.…”
Section: Climate Forcingmentioning
confidence: 99%
“…The most prominent of these proposed solutions has been planetary albedo modification schemes, where the amount of incoming solar radiation reflected back to space is artificially increased by some method. Such schemes have included introducing sulphate aerosols into the stratosphere globally (e.g., Irvine et al, 2016;McCusker et al, 2012;Rasch et al, 2008), as well as specifically in the Arctic (e.g., Jackson et al, 2015;Lee et al, 2021;Robock et al, 2008), marine cloud brightening (e.g., Kravitz et al, 2014;Latham, 1990), land albedo modification (e.g., Irvine et al, 2011) or sunshade geoengineering (e.g., Kravitz et al, 2013). There have also been geoengineering proposals focused on the Arctic.…”
mentioning
confidence: 99%